Diverse prehistoric cattle husbandry strategies in the forests of Central Europe - Gillis, Rosalind E; Kendall, Iain P; Roffet-Salque, Mélanie; Zanon, Marco; Anders, Alexandra; Arbogast, Rose-Marie; Bogucki, Peter; Brychova, Veronika; Casanova, Emmanuelle; Classen, Erich; Csengeri, Piroska; Czerniak, Lech; et al. (Nature ecology & evolution, 2025)
During the sixth millennium BCE, the first farmers of Central Europe rapidly expanded across a varied mosaic of forested environments. Such environments would have offered important sources of mineral-rich animal feed and shelter, prompting the question: to what extent did early farmers exploit forests to raise their herds? Here, to resolve this, we have assembled multi-regional datasets, comprising bulk and compound-specific stable isotope values from zooarchaeological remains and pottery, and conducted cross-correlation analyses within a palaeo-environmental framework. Our findings reveal a diversity of pasturing strategies for cattle employed by early farmers, with a notable emphasis on intensive utilization of forests for grazing and seasonal foddering in some regions. This experimentation with forest-based animal feeds by early farmers would have enhanced animal fertility and milk yields for human consumption, concurrently contributing to the expansion of prehistoric farming settlements and the transformation of forest ecosystems. Our study emphasizes the intricate relationship that existed between early farmers and forested landscapes, shedding light on the adaptive dynamics that shaped humans, animals and environments in the past.
Keywords: History, Ancient; chov zvířat; Evropa; Archaeology; Europe; zvířata; dějiny starověku; skot; lesy; Animal Husbandry; archeologie; Forests; Cattle; Animals